Come hell or highball : a mystery - Chance, Maia (Chance, Maia. Discreet Retrieval Agency mystery., 2015)
"31-year-old society matron Lola Woodby has survived her loveless marriage with an unholy mixture of highballs, detective novels, and chocolate layer cake, until, her husband dies suddenly, leaving her his fortune...or so Lola thought. As it turns out, all she inherits from Alfie is a big pile of debt. Pretty soon, Lola and her stalwart Swedish cook, Berta, are reduced to hiding out in the secret love nest Alfie kept in New York City. But when rent comes due, Lola and Berta have no choice but to accept an offer made by one of Alfie's girls-on-the-side: in exchange for a handsome sum of money, the girl wants Lola to retrieve a mysterious reel of film for her. It sounds like an easy enough way to earn the rent money. But Lola and Berta realize they're in way over their heads when, before they can retrieve it, the man currently in possession of the film reel is murdered, and the reel disappears. On a quest to retrieve the reel and solve the murder before the killer comes after them next, Lola and Berta find themselves navigating one wacky situation after another in high style and low company. Charming, witty, often laugh-out-loud funny, Maia Chance's Come Hell or Highball introduces a sparkling new voice in crime fiction"--